The effectiveness of a foot-care education program based on multi-theory model in diabetic patients with risk of foot ulceration: A randomized controlled trial protocol - Huiwen Xu; Chen Wu; Lingyan Zhang; Yangqin Ju; Jie Chen; Qian Hu; Shuang Qiu (PLoS ONE, 2026)
Background Diabetic foot ulcer (DFU) is one of the most common and serious complications of diabetes mellitus (DM). The high disability and fatality rates of DFU raise the importance of early medical treatment. However, delays in seeking medical treatment among DFU patients are common, emphasizing the need for targeted health education. This study aims to evaluate the effectiveness of a Multi-Theory Model (MTM)-based foot care education program on improving healthcare decision-making and foot care behaviors in diabetic patients with risk of foot ulceration. Method A multicenter randomized controlled trial will be employed. Diabetic patients at risk of foot ulceration will be recruited from two different tertiary hospitals in different cities. Eligible participants will be randomly allocated to receive either routine education and a foot-care handbook (control group) or comprehensive foot-care education based on MTM (intervention group). The intervention period will last for 4 weeks, followed by a 3-month post-intervention follow-up. Questionnaire data and clinical data will be collected at baseline, immediately after the 4-week intervention, and at the 3-month follow-up. The primary outcome will be pre-hospital delay intentions. Foot care knowledge, foot care self-efficacy, and foot care behaviors will be investigated using questionnaires. Clinical data, including blood glucose, blood pressure, and body mass index (BMI), will also be assessed. Discussion Based on the MTM, this study developed a comprehensive foot-care education program for diabetic patients at risk of foot ulceration. By integrating systematic, theory-driven educational components, the program may equips both hospitals and community health services with a structured approach to deliver targeted foot-care education. Trial registration The RCT registry number: ChiCTR2400082853, 09/04/2024.